In-situ measurement of tension and contact forces for weaving process monitoring: Application to 3D interlock. (November 2019) - Bessette, Carole; Decrette, Mathieu; Tourlonias, Michel; Osselin, Jean-François; Charleux, François; Coupé, Dominique; Bueno, Marie-Ange
Abstract: This study is focused on the monitoring of 3D interlock weaving, which is a process used for structural composite reinforcements. As high-density weaving leads to significant damage on warp tows, the standard execution of the process is impacted. To increase the production rate, tow-to-tow interactions need to be clearly understood, which is the aim of in-situ measurements on a sequential weaving loom. Tension and contact force between tows were measured using specific sensors. Great differences in tension and contact force were highlighted as a function of the type of crossing during the weaving cycle. Specific tow crossings generate very high peaks of tension and contact force. A significant difference has been noticed between the impact of the raising and lowering of tows during shedding motion on the tension and force values. A spectral analysis of the tension signal has shown an interesting potential for indirect tow damage monitoring and detection.